2017
DOI: 10.1002/jctb.5308
|View full text |Cite
|
Sign up to set email alerts
|

Microbial fuel cells for polishing effluents of anaerobic digesters under inhibition, due to organic and nitrogen overloads

Abstract: BACKGROUND: Bioelectrochemical systems have been proposed as a possible polishing step for anaerobic digestion (AD). They can also be useful to overcome AD instability in case of AD inhibition while, at the same time recovering ammonia. Continuous assays with a microbial fuel cell (MFC) fed with digested pig slurry were performed to evaluate its operation during malfunction periods of the AD reactor and its feasibility as a strategy to recover ammonia, either by introducing volatile fatty acid (VFA) pulses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…On the second hand, BES can operate with low organic loading rates and may be used to polish the effluent of the AD [16][17][18] or even to absorb higher organic concentrations in the digestates due to AD destabilisation or inhibition [18,19]. Previous work has shown that integrated or multi-step systems can increase the energy production from complex substrates [4].…”
Section: mentioning
confidence: 99%
“…On the second hand, BES can operate with low organic loading rates and may be used to polish the effluent of the AD [16][17][18] or even to absorb higher organic concentrations in the digestates due to AD destabilisation or inhibition [18,19]. Previous work has shown that integrated or multi-step systems can increase the energy production from complex substrates [4].…”
Section: mentioning
confidence: 99%
“…Bioelectro-Fenton (bio-E-Fenton) as state-of-the-art technology was first proposed by Feng et al, 171 this concept is thus made possible by using the bio-electrons that have been produced from the microbial metabolism to drive an E-Fenton process. 172 Typical bio-E-Fenton systems are integrated MFC-Fenton and MEC-Fenton. Bio-E-Fenton has been studied for removing biorefractory organic pollutants.…”
Section: Bioelectro-fenton Systemmentioning
confidence: 99%
“…These systems currently are being studied for a wide range of potential applications such as recalcitrant pollutant removal, chemical synthesis, resource recovery and biosensors . For example, reduction of hexavalent chromium, ammonia recovery, remediation of xenobiotics, remediation of toxic metal contaminated soil, sulfate reduction or polishing effluents of anaerobic digesters are some of the applications reported recently for BES. Moreover, the generation of different products such as electricity, hydrogen, methane, biofuels, desalinated water or high‐value chemical products already has been reported.…”
Section: Introductionmentioning
confidence: 99%